Review: InsectsA Source of Safe and Sustainable Food? Jein (Yes and No) - Nils Th. Grabowski; Amir Abdulmawjood; Fatma Acheuk; Karol Barragn Fonseca; Ty Chhay; Eraldo Medeiros Costa Neto; Maurizio Ferri; Jonathan Franco Olivas; Delia Guillermina Gonzlez Aguilar; Sath Keo; Rachakris Lertpatarakomol; Phalla Miech; et al. (My University, 2022)
For almost a decade, edible insects have become promoted on a wider basis as one way to combat world hunger and malnourishment, although attempts to do so have a longer history. Contemporary researchers and consumers, particularly those without an entomophagous background, have been rising safety and sustainability concerns. The present contribution seeks a substantiated answer to the question posed above. The possible answer consists of different factors that have been taken into consideration. First, the species and its life cycle. It is mandatory to realize that what is labeled as “edible insects” stands for more than 2,140 animal species, not counting other edible, non-crustacean arthropods. Their life cycles are as diverse as the ecological niches these animals can fill and last between some days to several years and many of them may—or may not—be reproduced in the different farming systems. Second, the level of knowledge concerning the food use of a given species is important, be it traditional, newly created by research, or a combination of both. Third, the existence of a traditional method of making the use of the insect safe and sustainable, ideally from both the traditional and the modern points of view. Fourth, the degree of effectiveness of these measures despite globalization changes in the food-supplying network. Fifth, farming conditions, particularly housing, feeding (type, composition, and contaminants), animal health and animal welfare. Sixth, processing, transport, and storage conditions of both traditional and novel insect-based foodstuffs, and seventh, consumer awareness and acceptance of these products. These main variables create a complex web of possibilities, just as with other foodstuffs that are either harvested from the wild or farmed. In this way, food safety may be reached when proper hygiene protocols are observed (which usually include heating steps) and the animals do not contain chemical residues or environment contaminants. A varying degree of sustainability can be achieved if the aforementioned variables are heeded. Hence, the question if insects can be safe and sustainable can be answered with “jein,” a German portmanteau word joining “yes” (“ja”) and “no” (“nein”).
Keywords: Insect Utilization and Effects